Heat cost allocation in energy efficient multi-apartment buildings. Issue 1 (1st January 2018) - Siggelsten, Simon
Abstract: The purpose of this study is to analyse the accuracy of allocating heat cost by measuring the delivered amount of heat in an energy-efficient multi-apartment building with underfloor heating. The main issue with heat cost allocation is heat transfer between adjacent apartments, which means that purchased heat might not be the same as the used heat in an apartment. This study analyses the fluctuation of the energy consumption in 31 apartments during a time span of one month over four years. The fluctuation is presented as the standard deviation of the spreading. Most of the apartments show a large fluctuation, with the average standard deviation measuring at 3.47 kWh/m 2 . However, when examining the entire building as a complete unit, the standard deviation only amounts to 0.13 kWh/m 2 . The result indicates significant heat transfer between adjacent apartments.